“Diseño y estudio de un sistema de iluminación para el estadio de la Universidad Técnica de Cotopaxi campus Salache” - Bonilla Gancino, Alex Isrrael (2021)
This technological proposal is aimed at developing the design and study of a lighting system for the stadium of the Technical University of Cotopaxi Campus Salache, through a technical analysis, the sketch is made in the DIAlux 4.13 software, taking into account the characteristics of the infrastructure. physical location, the energy capacity of the facilities, the focus of light on strategic sectors of the playing field or sports practice site according to the technical specifications of FIFA that refer to football stadiums and the CONELEC regulations with regarding public lighting of sports venues. The development of this research aims to extend the operating hours to daytime and nighttime to optimize and take advantage of light resources reducing energy consumption, using luminaires with efficient and economical technology for which factors such as load, Calculation of the transformer applying the INEN 1-154, NEC 11 regulation. This project is of great importance for the university community due to the economic and operational benefits it sees in its objectives, since at the moment only the stadium facilities work with the daylight for classes and sports activities, due to which its subsequent implementation would provide a practical advantage for the University, being used not only for the use of the university community, but to make it available to the entire sports community of the canton, the province and the country.